ANALISIS PERAN KEBIJAKAN FISKAL DAN MONETER DALAM PEREKONOMIAN TERBUKA INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Mery Aminita; Oktavia Pusvita Sari; Agung Darmawan; Zebron Zebron; Verdi Verdi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Indonesia’s open economy has become increasingly influenced by international trade dynamics, capital movements, exchange rate fluctuations, and various global economic shocks. Under these circumstances, fiscal and monetary policies constitute the primary instruments for maintaining economic stability and promoting national economic growth. This study aims to analyze the roles and effectiveness of fiscal and monetary policies in Indonesia’s open economy through a Systematic Literature Review (SLR) approach. The study adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and reviewed scientific articles published between 2015 and 2026. The review process involved identification, screening, eligibility assessment, and synthesis of relevant studies. The findings reveal that fiscal policy contributes to increasing aggregate demand, encouraging investment, and accelerating economic recovery, while monetary policy plays an important role in controlling inflation, maintaining exchange rate stability, and preserving financial system stability. Furthermore, the study highlights that coordination between fiscal and monetary policies is essential for enhancing the effectiveness of economic management in an open economy. Therefore, strengthening policy coordination is necessary to address global economic challenges and achieve sustainable economic growth.